Hierarchical structured α-Al2O3 supported S-promoted Fe catalysts for direct conversion of syngas to lower olefins1. Issue 42 (25th May 2015) - Zhou, Xiangping; Ji, Jian; Wang, Di; Duan, Xuezhi; Qian, Gang; Chen, De; Zhou, Xinggui
<x xml:space="preserve">Abstract</x> Fe/α-Al2O3-H catalyst promoted using appropriate sulfur content exhibits not only enhanced FTO performance, but also increased resistance against carbon deposits.